We know the derivative of ex, which is ex.
(ex)' = ex
We can find the derivative of e-x using chain rule.
If y = e-x, find ᵈʸ⁄dₓ.
y = e-x
Let t = -x.
Then, we have
y = et
Now, y = et and t = -x. That is, y is a function of t and t is a function of x.
By chain rule, the derivative of y with respect to x,
Substitute y = et and t = -x.
Substitute t = -x.
Kindly mail your feedback to email@example.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
May 26, 23 12:27 PM
May 21, 23 07:40 PM
May 20, 23 10:53 PM